Subcellular fractionation and localization studies reveal a direct interaction of the fragile X mental retardation protein (FMRP) with nucleolin. - Mohamed S Taha; Kazem Nouri; Lech G Milroy; Jens M Moll; Christian Herrmann; Luc Brunsveld; Roland P Piekorz; Mohammad R Ahmadian (PLoS ONE, 2014)
Fragile X mental Retardation Protein (FMRP) is a well-known regulator of local translation of its mRNA targets in neurons. However, despite its ubiquitous expression, the role of FMRP remains ill-defined in other cell types. In this study we investigated the subcellular distribution of FMRP and its protein complexes in HeLa cells using confocal imaging as well as detergent-free fractionation and size exclusion protocols. We found FMRP localized exclusively to solid compartments, including cytosolic heavy and light membranes, mitochondria, nuclear membrane and nucleoli. Interestingly, FMRP was associated with nucleolin in both a high molecular weight ribosomal and translation-associated complex (≥6 MDa) in the cytosol, and a low molecular weight complex (∼200 kDa) in the nucleoli. Consistently, we identified two functional nucleolar localization signals (NoLSs) in FMRP that are responsible for a strong nucleolar colocalization of the C-terminus of FMRP with nucleolin, and a direct interaction of the N-terminus of FMRP with the arginine-glycine-glycine (RGG) domain of nucleolin. Taken together, we propose a novel mechanism by which a transient nucleolar localization of FMRP underlies a strong nucleocytoplasmic translocation, most likely in a complex with nucleolin and possibly ribosomes, in order to regulate translation of its target mRNAs.